Border Encounters between the Neighbours in Central Asia: the Case of Vorukh (Халықаралық қатынастар және халықаралық құқық сериясы, 2023)
The current situation in the Vorukh enclave, located in the Ferghana Valley, whose borders are clearly disputed by the two Central Asian republics, Kyrgyzstan and Tajikistan, seems rather complicated. Like many other enclaves within Central Asia, Vorukh has high unemployment rates and other socio-economic issues endemic for this region. The enclave turned into the major ignition point for border clashes between the Kyrgyz and Tajik forces for the last few decades.The article examines both tangible and intangible factors that contribute to the tensions between the two states. Factors of ethnic and national identification are surveyed to understand certain actions, views and values of the belligerents during violent border incidents. The border incidents between Bishkek and Dushanbe might be described as interstate, intergovernmental and in some cases interethnic collision. One of the most important steps to resolve the matter is to engage in constructive dialogue and negotiations between the parties involved. This would require a feasible platform for open discussions of the issues, concerns, and grievances of each group, and political willingness to work towards mutually acceptable solutions.This research is funded by the Science Committee of the Ministry of Science and Higher Education of the Republic of Kazakhstan (Grant No. BR18574168).Keywords: Central Asia, Kyrgyz-Tajik border clashes, Kyrgyzstan, Tajikistan, Vorukh enclave.